'Power to the People, to the people': Training for social prescribers improves support of persistent pain. Issue 3 (June 2023) - Corline, Alex; Cole, Frances; Trewern, Louise; Penlington, Chris
Introduction: Supported self-management is an important aspect of managing pain, however widely held beliefs about the biomedical nature of pain and limited time availability can make it a tricky concept to introduce to patients. Social prescribers are in an ideal position to support self-management of pain if appropriate training is available to support them. This study aimed to evaluate training for social prescribers and to explore their opinions and experiences about providing self-management support. Methods: This was a mixed methods study. Repeated measures t-tests were used to compare the reported confidence of attendees in supporting different facets of self-management before and after the training. Thematic analysis of interviews was used to develop a deeper understanding of how participants related the training to their work with patients. Results: Average confidence improved in all aspects of supporting self-management, and particularly with regard to supporting understanding pain, acceptance, pacing, setting goals, sleep and managing setbacks. Challenges were identified around explaining pain in an accurate and accessible way in order to provide a meaningful rationale for self-management. Conclusion: Training for social prescribers in self-management support is feasible and leads to improvements in self-reported confidence. Further research is needed to determine the impact on patients and over a longer period of time.